Effect of Silica Fume on Steel Slag Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
In India, the production of steel slag is about  12 million tons in the steel industries and we can use in our  concrete as a waste material. Concrete is most commonly  and widely used building material used in all around the  world. Concrete is the mixture of cement, sand, aggregates  (fine and coarse), and water. The utilization of concrete is  continuously increasing due to which there is a great effect  on natural resources. There are many numbers of by products (like, steel slag, silica fume, fly ash, etc.) that are  produced during the production or the manufacturing of  material like steel, silicon metal, etc. In the present study  effect of silica fume on steel slag concrete has been carried  out on M25 grade of concrete by varying percentage of steel  slag i.e. 45%, 50% and 55% and constant value of silica  fume i.e. 10%. From the study it has been observed that the  compressive strength decreases while increases the  percentages of steel slag. Therefore, up to 45% replacement  of steel slag with the fine aggregates and 10% replacement  of silica fume with cement give best result and after that the  strength will decreases.
Keywords: Steel Slag; Silica Fume; Concrete; Compressive Strength; w/c ratio